Expanding applications of pulmonary MRI in the clinical evaluation of lung disorders: Fleischner Society position paper - Hatabu, Hiroto; Ohno, Yoshiharu; Gefter, Warren B.; Parraga, Grace; Madore, Bruno; Lee, Kyung Soo; Altes, Talissa A.; Lynch, David A.; Mayo, John R.; Seo, Joon Beom; Wild, Jim M.; van Beek, Edwin J. R.; et al. (Radiology, 2020)
Pulmonary MRI provides structural and quantitative functional images of the lungs without ionizing radiation, but it has had limited clinical use due to low signal intensity from the lung parenchyma. The lack of radiation makes pulmonary MRI an ideal modality for pediatric examinations, pregnant women, and patients requiring serial and longitudinal follow-up. Fortunately, recent MRI techniques, including ultrashort echo time and zero echo time, are expanding clinical opportunities for pulmonary MRI. With the use of multicoil parallel acquisitions and acceleration methods, these techniques make pulmonary MRI practical for evaluating lung parenchymal and pulmonary vascular diseases. The purpose of this Fleischner Society position paper is to familiarize radiologists and other interested clinicians with these advances in pulmonary MRI and to stratify the Society recommendations for the clinical use of pulmonary MRI into three categories: (a) suggested for current clinical use, (b) promising but requiring further validation or regulatory approval, and (c) appropriate for research investigations. This position paper also provides recommendations for vendors and infrastructure, identifies methods for hypothesis-driven research, and suggests opportunities for prospective, randomized multicenter trials to investigate and validate lung MRI methods. (C) RSNA, 2020